Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am studying for my exam in real analysis and I am having difficulties with some of the material, I know that the following should be solved by using the counting measure and LDCT, but I don't know how.

For $\alpha>0,$ Calculate $$\lim_{n\to\infty}\sum_{k=1}^{\infty}\frac{(-1)^{k}\arctan(n^{2}k)}{n^{\alpha}+k^{3/2}}$$

I would greatly appreciate it if in the answers you can include all the details about the theorems used (since there is a high importance for the arguments for why we can do what we do in each step, and I don't understand the material good enough to be able to understand that some step is actually not trivial and uses some theorem)

share|cite|improve this question
By "arctg", do you by any chance mean "arctangent", which can be written either as "arctan", "atan", or "$\tan^{-1}$"? (someone has edited it to say that. Is it what you intended?) – Glen O Apr 1 '13 at 12:45
@GlenO - Yes, this is what I mean. thanks for asking it to clarify, and sorry for the wrong spelling of the name of the function – Belgi Apr 1 '13 at 12:48
up vote 4 down vote accepted

Note that for terms of serie $\sum_{k=1}^n \frac{(-1)^{k}\arctan(n^{2}k)}{n^{\alpha}+k^{3/2}}$ we have \begin{align} \left|\frac{(-1)^{k}\arctan(n^{2}k)}{n^{\alpha}+k^{3/2}}\right| = & \left| \frac{\arctan(n^{2}k)}{n^{\alpha}+k^{3/2}}\right| \\ \leq & \left| \frac{2\pi}{n^{\alpha}+k^{3/2}}\right| \\ = & \left| \frac{\pi}{\frac{n^{\alpha}+k^{3/2}}{2}}\right| \\ \leq & \frac{\pi}{\sqrt[2\,]{n^{\alpha}\cdot k^{3/2}}} \\ = & \frac{\pi}{n^{\frac{\alpha}{2}}\cdot k^{3/4}} \\ = & \frac{1}{n^{\frac{\alpha}{2}}}\frac{\pi}{k^{3/4}} \end{align} Then $$ 0\leq \left| \sum_{k=1}^n \frac{(-1)^{k}\arctan(n^{2}k)}{n^{\alpha}+k^{3/2}}\right|\leq \sum_{k=1}^n\left|\frac{1}{n^{\frac{\alpha}{2}}}\frac{\pi}{k^{3/4}}\right| $$ By Squeeze Theorem for Sequences, $\sum_{k=1}^n\left|\frac{1}{n^{\frac{\alpha}{2}}}\frac{\pi}{k^{3/4}}\right|\to 0$ (for all $\alpha>0$) implies $\left|\sum_{k=1}^n \frac{(-1)^{k}\arctan(n^{2}k)}{n^{\alpha}+k^{3/2}}\right| \to 0$

share|cite|improve this answer
Can you please explain the second inquality and the last line: what is the parameter that tends to infinity in the beginning and the "implies" part – Belgi Apr 1 '13 at 13:32
@Belgi $|\arctan(x)|\leq \frac{\pi}{2}\leq 2\pi$. Remember of graphic of function $\arctan(x)$. – MathOverview Apr 1 '13 at 13:33
@Belgi, Sorry. The second inequality is aritimetic-geometric inequality: $\sqrt[2\,]{a\cdot b}\leq \frac{a+b}{2}$ implies $\frac{1}{\frac{a+b}{2}}\leq \frac{1}{\sqrt[2\,]{a\cdot b}}$ – MathOverview Apr 1 '13 at 13:36
Perhaps I'm deeply wrong, but $\sum^{n}_{k=1}\biggr|\frac{1}{n^{\frac{\alpha}{2}}}\frac{\pi}{k^{3/4}}\biggr|=(‌​\pi/n^{\alpha/2})\sum^{n}_{k=1}\biggr|\frac{1}{k^{3/4}}\biggr|$. Assuming, say, $\alpha=0.00001$, we have $\frac{\pi}{n^{\alpha/2}}\sum^{n}_{k=1}\biggr|\frac{1}{k^{3/4}}\biggr|\to\infty$ as $n\to\infty$. – Johnny Westerling Apr 1 '13 at 16:30
Indeed, the series with respect ot $k$ has to be evaluated in full, independently on $n$. So, calling $N$ the upper limit, we first have to send $N\to\infty$ and then we can send $n\to\infty$. Unfortunately, when sending $N\to\infty$ we get a divergent series, so we cannot conclude anything. – bartgol Mar 14 at 20:36

Let $a(n,k):=(-1)^k\frac{\arctan(n^2k)}{n^{\alpha}+k^{3/2}}$; then $|a(n,k)|\leqslant \frac{\pi}{2k^{3/2}}$ for each $n$, hence $$\left|\sum_{k=1}^{+\infty}a(n,k)\right|\leqslant \sum_{k=1}^N|a(n,k)|+\frac{\pi}2\sum_{k\geqslant N+1}k^{-3/2},$$ which gives that for each integer $N$, $$\limsup_{n\to +\infty}\left|\sum_{k=1}^{+\infty}a(n,k)\right|\leqslant\sum_{k\geqslant N+1}k^{-3/2}.$$ Conclude (we actually used dominated convergence theorem).

share|cite|improve this answer
Can you please explain how you got the line after "which gives that for" and where did you use LDCT ? This means that the sum is $0$, right ? – Belgi Apr 1 '13 at 13:04
Taking the $\limsup$ on both sides, the first sum converges to $0$ because we considered finitely many terms which converge to $0$. We took bound which doesn't depend on $n$. – Davide Giraudo Apr 1 '13 at 13:08
@Davide Giraudo It was not to calculate the value of the serie? – MathOverview Apr 1 '13 at 13:08
@E.Costa It seems we just need the limit as $n\to +\infty$. – Davide Giraudo Apr 1 '13 at 13:09
@Belgi I don't think so... for each $k$, we have that $(-1)^{k}\frac{\arctan{n^{2}k}}{n^{\alpha}+k^{3/2}}\to 0$ as $n\to\infty$, because the numerator tends to $\pi/2$ for $k>0$ and in the denominator we have $k^{3/2}$, which does not change, and $n^\alpha$, which tends to $\infty$ for $\alpha>0$... – Johnny Westerling Apr 1 '13 at 16:55

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.